Prevention of Cervical Cancer. Guideline of the DGGG and the DKG (S3 Level, AWMF Register Number 015/027OL, December 2017) – Part 2 on Triage, Treatment and Follow-up - Hillemanns, Peter; Friese, Klaus; Dannecker, Christian; Klug, Stefanie; Seifert, Ulrike; Iftner, Thomas; Hädicke, Juliane; Löning, Thomas; Horn, Lars; Schmidt, Dietmar; Ikenberg, Hans; Steiner, Manfred; Freitag, Ulrich; Siebert, Uwe; Sroczynski, Gaby; Sauerbrei, Willi; Beckmann, Matthias W.; Gebhardt, Marion; Friedrich, Michael; Münstedt, Karsten; Schneider, Achim; Kaufmann, Andreas; Petry, K. Ulrich; Schäfer, Axel P. A.; Pawlita, Michael; Weis, Joachim; Mehnert, Anja; Fehr, Mathias; Grimm, Christoph; Reich, Olaf; Arbyn, Marc; Kleijnen, Jos; Wesselmann, Simone; Nothacker, Monika; Follmann, Markus; Langer, Thomas; Jentschke, Matthias (Geburtshilfe und Frauenheilkunde, 2019)
Aims Annual opportunistic screening for cervical carcinoma has been done in Germany since 1971. The creation of this S3 guideline meets an important need, outlined in the National Cancer Plan, with regard to screening for cervical cancer, as this guideline aims to provide important information and support for planned organized screening for cervical cancer in Germany.Methods With the financial support of German Cancer Aid, 21 professional societies developed evidence-based statements and recommendations (classified using the GRADE system) for the screening, management and treatment of precancerous conditions of the cervix. Two independent scientific institutes compiled systematic reviews for this guideline.Recommendations The second part of this short summary deals with the triage, treatment and follow-up care of cervical dysplasia. With regard to those women who do not participate in screening, the guideline authors recommend sending out repeat invitation letters or an HPV self-collection kit. Colposcopy should be carried out for further investigation if cytology findings are Pap II-p and HPV test results are positive or if the results of an HPV 16 or HPV 18 screening test are positive. A single abnormal Pap smear should be triaged and investigated using HPV testing or p16/Ki67 dual staining.Ziele Seit 1971 erfolgt in Deutschland die jährliche, opportunistische Früherkennungsuntersuchung des Zervixkarzinoms. Durch die Etablierung dieser S3-Leitlinie wird zum einen eine wichtige Forderung des Nationalen Krebsplans zum Zervixkarzinom-Screening erfüllt. Zum anderen kann die S3-Leitlinie wesentliche Informationen und Hilfestellungen für das geplante organisierte Zervixkarzinomscreening in Deutschland geben.Methoden Mit finanzieller Unterstützung durch die Deutsche Krebshilfe wurden durch 21 Fachgesellschaften evidenzbasierte Statements und Empfehlungen (GRADE-System) zu Screening, Management und Behandlung von Zervixkarzinom-Vorstufen erarbeitet. Zwei unabhängige wissenschaftliche Institute haben systematische Reviews für diese Leitlinie erarbeitet.Empfehlungen Der zweite Teil dieser Kurzzusammenfassung behandelt u. a. Abklärung, Therapie und Nachbetreuung zervikaler Dysplasien. Im Hinblick auf Nichtteilnehmerinnen am Screening empfiehlt die Leitliniengruppe erneute Einladungsschreiben oder eine HPV-Selbstabnahme. Ab einer Zytologie von Pap II-p in Kombination mit einem positiven HPV-Befund sollte eine Kolposkopie zur weiteren Abklärung durchgeführt werden, ebenso bei einem positiven HPV 16 oder HPV 18 Screening Test. Ein alleiniger auffälliger Pap-Abstrich sollte eine Triage mittels HPV-Test oder p16/Ki67 Dual-stain zur Folge haben.
Keywords: cervical cancer; cervical intraepithelial neoplasia (CIN); cervical precancerous condition; HPV